Persepsi Pelajar Terhadap Penggunaan Animasi dalam Pembelajaran Bahasa Arab - Che Hat, Norhayati; Sha'ari, Shaferul Hafes; Abdul Hamid, Mohd Fauzi (Sains Humanika, 2013)
The implementation of animation as a teaching tool in learning Arabic language is indeed an innovation to create an environment that will promote students’ interest. This article will be discussing students’ perception toward using animation as teaching tool in learning Arabic language. A set of quantitative questionnaire is built to gain data. These data will then be analyzed descriptively to find out the distribution of frequency, percentage and mean. The result of this study indicates that the students have high perception and respond positively toward the using of animation as teaching tool in learning Arabic language with average value of 4.34. The study supports that the animation is an additional practical way to teach Arabic language and contribute in attracting students’ interest to master it.